Music--Motion and Emotion : the Developmental-Integrative Model of Music Therapy. - Sekeles, Chava (Barcelona Publishers, 2014)
Professor Shiloah of Hebrew University describes this unique model of music therapy as a "synthesis of diverse theories elaborated over recent decades by prominent specialists, as well as the views developed by Dr. Sekeles herself in the course of her extensive empirical and professional experience." The book integrates discussion of three inter-related topics: music in traditional healing rituals, the Developmental-Integrative model in Music Therapy, and five case histories demonstrating the model.